The role of green human resourches management as mediation in the effect of organizational culture on employee performance - Muhamad Ekhsan; Ryani Dhyan Parashakti (Enrichment : Journal of Management, 2023)
The purpose of this study is to evaluate the role of GRHRM as a mediator in influencing the relationship between organizational culture and employee performance. This research will use a quantitative approach by distributing questionnaires to respondents in several manufacturing companies in the industrial area in Cikarang. The questionnaire will contain items related to organizational culture, GRHRM, and employee performance. Data analysis will use path coeffiecient to evaluate the role of GRHRM as mediation in influencing the relationship between organizational culture and employee performance. The research shows that the implementation of sustainable GHRM practices can increase employee job satisfaction. Employees who feel involved in the organization's sustainability practices tend to be more satisfied with their jobs and have a more positive attitude towards the company. The implication of this research is that GHRM helps organizations to adopt environmentally friendly practices and build a culture that supports sustainability. This can result in long-term benefits, such as reduced carbon emissions, energy savings, waste reduction, and preservation of natural resources. Employees who engage in these practices feel more satisfied with their jobs and are more motivated to contribute to the organization's sustainability goals.